Mangoes : a review - Prinsley, Roslyn Tamara, ed. (CSC LondonGB, 1987)
Collection of review papers on markets for mangoes from the Caribbean; mango production; development and adaptation of methods for control of antracnose; maturity indicies for quality control and harvest maturity; ripening and post harvest treatment; and developments in technology for processing of mangoes.